Occurrence of Millotellina (Myriapoda, Symphyla) in China with the description of two new species - Jin, Ya-Li; Bu, Yun (Zootaxa, 2019)
The genus Millotellina is recorded from China for the first time. Two new species, Millotellina centralis sp. n. and Millotellina bambusinus sp. n., from Guangxi Province of Southwest China are described and illustrated. Millotellina centralis sp. n. is characterized by the presence of single median ventral processes posterior to the coxal sacs of legs 4–10, half-way between successive pairs of legs and located in the center, and a thick frontal seta on the first leg. Millotellina bambusinus sp. n. is characterized by the single median ventral processes inserted between the coxal sacs of legs 5–10, palp of the first maxilla with three pointed branches, and cerci narrowed abruptly in the distal part. An updated key to the species of the genus is also provided.